2006
DOI: 10.1103/physrevb.74.134305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure on the Raman modes of antimony

Abstract: The effect of pressure on the zone-center optical phonon modes of antimony in the A7 structure has been investigated by Raman spectroscopy. The Ag and Eg frequencies exhibit a pronounced softening with increasing pressure, the effect being related to a gradual suppression of the Peierls-like distortion of the A7 phase relative to a cubic primitive lattice. Also, both Raman modes broaden significantly under pressure. Spectra taken at low temperature indicate that the broadening is at least partly caused by phon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
82
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 55 publications
17
82
1
Order By: Relevance
“…Our experiments demonstrate that under compressive load (decrease in volume) amorphous GeSb crystallizes, forming crystalline phases analogous to Sb (22,23), which is known to crystallize explosively near room temperature (24). As shown in the X-ray diffraction data and Raman spectra under pressure (see Materials and Methods), crystallization (appearance of A7 structure Bragg peaks in Figs.…”
Section: Resultssupporting
confidence: 58%
“…Our experiments demonstrate that under compressive load (decrease in volume) amorphous GeSb crystallizes, forming crystalline phases analogous to Sb (22,23), which is known to crystallize explosively near room temperature (24). As shown in the X-ray diffraction data and Raman spectra under pressure (see Materials and Methods), crystallization (appearance of A7 structure Bragg peaks in Figs.…”
Section: Resultssupporting
confidence: 58%
“…Such low frequencies have only been observed in pressure-dependent experiments in the GPa range. 28 The observed nonthermal phonon softening is comparable to the one measured in the time domain with similar electronic excitation densities clearly demonstrating that the electronic screening of the crystal potential induces a large phonon softening and that anharmonicity only plays a minor role, if any. One of the most striking observations it that the line shape for the first few picoseconds after excitation is substantially different for low and high excitation densities.…”
supporting
confidence: 65%
“…Another possibility would be that the new phase corresponds to one of the phases observed at high pressures ͑Ͼ8 GPa͒. 28 However, in that case one would expect a new mode on the high energy side of L1, which is not the case.…”
mentioning
confidence: 99%
“….T his softening of the optical phonons in DFT calculations has been observed before, [14] and appears to be related to the strong electron-lattice interaction and the negative Grüneisen parameter in antimony [11] and similar materials,such as bismuth.…”
mentioning
confidence: 52%
“…[11] Correlation of AFM and statistical Raman microscopy (SRM) [12] in apolydisperse sample revealed that flakes with an apparent thickness below about 70 nm (ca. 17 layers) hardly show any measurable Raman signal (Figure 4b).…”
Section: Zuschriftenmentioning
confidence: 99%